1994
DOI: 10.1108/09564239410074349
|View full text |Cite
|
Sign up to set email alerts
|

Making Relationship Marketing Operational

Abstract: Based on a research project with the purpose of defining the essence and scope of relationship marketing (RM). The marketing mix theory, which constitutes the prevailing approach to marketing, is made operational through the definition of the 4Ps and extensions of these. The core is a presentation of 30 relationships, the 30Rs, as a way of making the RM philosophy more operational and generally applicable. The 30Rs provide a basis for companies to work out their own specific relationship portfolio as part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
298
0
31

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(336 citation statements)
references
References 11 publications
7
298
0
31
Order By: Relevance
“…Page and Siemplenski (1983, p. 89) also related systems marketing to developments within general marketing, arguing that product firms "are turning to the marketing of systems to satisfy the more extended and complex needs of their customers". Even though they did not expand this discussion further, it is closely related to more recent debates (Cova & Salle, 2008;Windahl & Lakemond, 2006;2010), linking solutions to the service marketing discourse of the Nordic School of Marketing and the emphasis on longterm relationships (Grönroos, 2011;Gummesson, 1994;Normann, 2001), and a servicedominant view on value (Vargo & Lusch, 2004). Arguably, system selling now extends beyond solving customers' operational problems to include more strategic forms of marketing, based on so-called 'solution selling' (Davies et al, 2007;Helander & Möller, 2008).…”
Section: Back To the Roots: Systems Selling And Industrial Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Page and Siemplenski (1983, p. 89) also related systems marketing to developments within general marketing, arguing that product firms "are turning to the marketing of systems to satisfy the more extended and complex needs of their customers". Even though they did not expand this discussion further, it is closely related to more recent debates (Cova & Salle, 2008;Windahl & Lakemond, 2006;2010), linking solutions to the service marketing discourse of the Nordic School of Marketing and the emphasis on longterm relationships (Grönroos, 2011;Gummesson, 1994;Normann, 2001), and a servicedominant view on value (Vargo & Lusch, 2004). Arguably, system selling now extends beyond solving customers' operational problems to include more strategic forms of marketing, based on so-called 'solution selling' (Davies et al, 2007;Helander & Möller, 2008).…”
Section: Back To the Roots: Systems Selling And Industrial Marketingmentioning
confidence: 99%
“…Empirically, this shift is frequently referred to as "service infusion" Ostrom et al, 2010) or as "servitization" (Vandermerwe & Rada, 1988;Visnjic Kastalli & Van Looy, 2013). Theoretically, marketing scholars emphasize the need for a 'service' perspective for all firms, arguing that service rather than goods (should) form the basis of economic exchange (Grönroos, 2011;Gummesson, 1994;Normann, 2001;Vargo & Lusch, 2004).…”
Section: From Products To Solutions: the Underlying 'Service Transitimentioning
confidence: 99%
“…The micro-entrepreneur's relationship-management competence determines the extent to which he or she can obtain the resources that are required for their step-change. In this process, microentrepreneurs need to scrutinize, prioritize, and establish the suitable mix of relationships necessary for achieving their goals (accessing resources) (Gummesson, 1994). As the relationships between actors are embedded in a social network, the literature on relationship marketing argues that the relation between entrepreneurs' relationship competence and access to resources is contingent on the configuration of all other stakeholders (Moura & Teixeira, 2010;Payne, Ballantyne, & Christopher, 2005).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…They may have to trade off the costs and benefits of the relationships. Entrepreneurs should know which relationships to invest in further or divest themselves of, and which relationships to keep on a transactional level because they lack reciprocal value (Gummesson, 1994;Moyes, Whittam, & Ferri, 2012). In the context of making a step-change, entrepreneurs may develop five activities to access resources and maintain a low cost of network maintenance: assessing relationship value, scanning relationship opportunities, developing new relations, continuing relationships, and abandoning former relations (Grönroos, 1994;Gummesson, 1987).…”
Section: The Role Of Relationship Managementmentioning
confidence: 99%
“…Studies have shown that there are up to as many as 45 characteristics that influences the overall relationship. Some of the most important characteristics for a successful relationship are cooperation, commitment, trust, power, consistency, adoption and attraction (Gummesson, 1994).…”
Section: Figurementioning
confidence: 99%